Crystallinity and Microstructural Versatility in the Spin‐Crossover Polymeric Material [Fe(Htrz)2(trz)](BF4). Issue 3 (12th December 2017) - Grosjean, Arnaud; Daro, Nathalie; Pechev, Stanislav; Etrillard, Céline; Chastanet, Guillaume; Guionneau, Philippe
Abstract : The room‐temperature microstructure of the spin‐crossover (SCO) 1D polymeric iron(II) compound [Fe(Htrz)2 (trz)](BF4 ) has been investigated by means of powder X‐ray diffraction and compared with the SCO features determined by magnetic measurements. The microstructural parameters, such as the sizes of the coherent domains, of a number of samples and their morphologies have revealed new features of this material. Heating can significantly improve the crystallinity of the material by doubling the coherent domain size, which may open a route to regenerating this system after the reported mechanical fatigue it undergoes after suffering numerous SCO cycles. In addition, the correlation between the length of the coherent domain and the SCO temperature shows that the longer the domains, that is, the longer the iron chains, the higher the SCO temperatures. Abstract : Links between microstructure, the length of the iron chains, and the spin‐crossover features are considered in particles of the 1D polymeric iron(II)‐based triazole compound [Fe(Htrz)2 (trz)](BF4 ).